PENGARUH AUDIT TENURE, PERGANTIAN AUDITOR DAN FINANCIAL DISTRESS PADA AUDIT DELAY PADA PERUSAHAAN CONSUMER GOODS - Praptika, Putu Yulia Hartanti; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
This study aims to determine the effect of audit tenure, auditor switching and financial distress on audit delay. This research was taken on Consumer Goods companies which are listed in Indonesia Stock Exchange in 2009-2014 period. Samples were selected by using random sampling method, with the number of observations of 144 samples. The data analysis technique which is used on this research is multiple regression analysis. The results showed that the auditor switching and financial distress have a positive effect on audit delay, while the audit tenure has no effect on audit delay.
Keywords: audit delay, audit tenure, auditor switching, financial distress